Sastra Cyber: Alternatif Komunikasi antara Karya Sastra dan Masyarakat Pembaca - Arif Hidayat (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2008)
The existence of cyberliterary is an impact of technology development. Cyberliterary become new alternativefor writer to communicate his works to people. From Indonesian literary domain, we can conclude that a writer capabilitydetermined by his work